2019
DOI: 10.21203/rs.2.10992/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The dishwasher rubber seal acts as a reservoir of bacteria in the home environment

Abstract: Bacteria that colonise the extreme environment of household dishwasher rubber seals were investigated using cultivation-dependent and metagenomic approaches. All 30 dishwashers investigated were colonised by various bacteria. Cultivation approaches resulted in 632 bacterial isolates in total, belonging to four phyla, eight classes, 40 genera and 74 species. The majority were Gram-positive, as solely Firmicutes (dominated by the Bacillus cereus group) and Actinobacteria. Gammaproteobacteria were primarily repre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…In dishwashers, no bacterial growth was detected after test runs except for the eco-program, thus cleaned dishes seem to be no source of the tested strains. However, ABR bacteria were isolated from rubber door seals and DW sieves and have already been identified as a source of pathogenic and opportunistic pathogenic bacteria and fungi (42,63,64). Zupančič et al (2019) determined a low phenotypic ABR potential in DW, which is confirmed by our study since less resistant strains were isolated compared to SD and WM.…”
Section: Abr Bacteria In Washing Machines and Dishwasherssupporting
confidence: 83%
See 1 more Smart Citation
“…In dishwashers, no bacterial growth was detected after test runs except for the eco-program, thus cleaned dishes seem to be no source of the tested strains. However, ABR bacteria were isolated from rubber door seals and DW sieves and have already been identified as a source of pathogenic and opportunistic pathogenic bacteria and fungi (42,63,64). Zupančič et al (2019) determined a low phenotypic ABR potential in DW, which is confirmed by our study since less resistant strains were isolated compared to SD and WM.…”
Section: Abr Bacteria In Washing Machines and Dishwasherssupporting
confidence: 83%
“…Previous studies revealed the presence of bla genes (26) and the correlation of multiresistance with intI1 (16) in the domestic environment, but no studies on the frequency distribution of bla genes and their co-occurrence in private households, especially in relation to phenotypic resistance, have been conducted so far. SD, WM and DW provide a good habitat for microbial communities with a steady nutrient supply in a humid environment, promoting bacterial growth and biofilm formation (39)(40)(41)(42). Besides, ABR bacteria and antibiotic residues have been detected in siphons of hospitals (43,44), indicating their occurrence in SD of domestic areas as well.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed the presence of bla genes ( 32 ) and the correlation of multiresistance with intI1 ( 15 ) in the domestic environment, but no studies on the quantitative prevalence of bla genes and their co-occurrence in private households, especially in relation to phenotypic resistance, have been conducted so far. SD, WM, and DW provide good habitats for microbial communities with a steady nutrient supply in a humid environment, promoting bacterial growth and biofilm formation ( 39 , 47 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…No bacterial growth was detected in dishwashers after test runs, except with the ecoprogram; thus, cleaned dishes do not seem to be a source of the tested strains. However, antibiotic-resistant bacteria were isolated from rubber door seals and DW sieves and have already been identified to be a source of pathogenic and opportunistic pathogenic bacteria and fungi ( 40 , 49 , 74 ). Zupančič et al ( 49 ) determined a low phenotypic ABR potential for strains from DW, a finding which was confirmed by our study, since fewer resistant strains were isolated from DW than from SD and WM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation